(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Congenital hypothyroidism (CH) is the most common neonatal endocrine disorder and a leading preventable cause of intellectual disability if not diagnosed and treated early. In Bangladesh, neonatal screening for CH was initiated in 1999 with support from the International Atomic Energy Agency using radioimmunoassay-based thyroid-stimulating hormone (TSH) measurement. Recent national data indicate an increasing incidence, highlighting the growing public health importance of CH in the country. This review explores the genetic landscape of CH in Bangladesh and its implications for diagnosis and personalized therapeutics. CH is genetically heterogeneous, broadly classified into thyroid dysgenesis and dyshormonogenesis. Mutations in genes such as TSHR, PAX8, NKX2-1, and FOXE1 are associated with thyroid dysgenesis, while defects in TPO, TG, DUOX2, and SLC5A5 underlie dyshormonogenesis. Available studies from Bangladesh, though limited, reveal a predominance of TPO gene mutations, indicating dyshormonogenesis as a significant contributor. Additional mutations in TSHR and NKX2.5 genes further highlight genetic diversity and complexity. Integrating genetic screening into neonatal CH programs in Bangladesh is essential for improving etiological diagnosis, enabling personalized treatment, and reducing healthcare burden. Strengthening national genomic research and screening strategies will be critical to advancing precision medicine in CH management. Bangladesh J. Nuclear Med. 28(2): 344-348, July 2025